2021
DOI: 10.1016/j.pmedr.2020.101277
|View full text |Cite
|
Sign up to set email alerts
|

An ecological model of drug and alcohol use and related harms among Aboriginal and Torres Strait Islander Australians: A systematic review of the literature

Abstract: Globally, Indigenous populations experience a disproportionately higher burden of disease related to substance use. Effective prevention of harm related to substance use is a key strategy for improving the health and wellbeing of Aboriginal and Torres Strait Islander peoples in Australia. To inform preventative approaches, this review synthesised the evidence of risk and protective factors of substance use and related harms among Aboriginal and Torres Strait Islander peoples. Eight peer-reviewed and two grey l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…To complement the recommendations derived from these formative consultations, we reviewed the academic and grey literature to determine the modifiable risk and protective factors for substance use among Aboriginal and Torres Strait Islander people, and the effective substance use prevention components identified internationally for Indigenous youth. A full description of the methods, search terms and findings of these systematic reviews are provided in the published review protocols [ 31 , 32 ] and results [ 19 , 33 ]. Table 3 summarises the implications for effective program development arising from these systematic reviews, and reviews of mainstream substance use prevention literature [ 16 , 29 ].…”
Section: Materials Methods and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To complement the recommendations derived from these formative consultations, we reviewed the academic and grey literature to determine the modifiable risk and protective factors for substance use among Aboriginal and Torres Strait Islander people, and the effective substance use prevention components identified internationally for Indigenous youth. A full description of the methods, search terms and findings of these systematic reviews are provided in the published review protocols [ 31 , 32 ] and results [ 19 , 33 ]. Table 3 summarises the implications for effective program development arising from these systematic reviews, and reviews of mainstream substance use prevention literature [ 16 , 29 ].…”
Section: Materials Methods and Resultsmentioning
confidence: 99%
“…Taking together, findings from our consultation and literature review in the information gathering phase indicated four key considerations in developing a culturally appropriate school-based prevention approach for Aboriginal and Torres Strait Islander adolescents: Adopt a comprehensive prevention strategy (beyond information provision) that is empowering, incorporates skills training and explores the impact of social influence and psychological distress on substance use; Combine core effective elements of mainstream programs with cultural elements, given the target factors for Aboriginal and Torres Strait Islander and non-Aboriginal adolescents are well aligned [ 33 ], and international evidence suggests that mainstream programs that are adapted to align with cultural identity and practices are effective in preventing substance-related harms among Indigenous adolescents [ 19 ]; Avoid stigma by developing a program for both Aboriginal and Torres Strait Islander and non-Aboriginal students that is inclusive, empowering and celebrates the cultural diversity within Australian classrooms; Align with the Australian schools’ curriculum and make use of technology for program delivery to capitalise on advantages of this delivery method, including student engagement, scalability and ease of implementation. …”
Section: Materials Methods and Resultsmentioning
confidence: 99%
See 3 more Smart Citations